Social distance towards female sex workers and its relations to authoritarianism, social dominance orientation and self-respect - Karić Tijana; Rašković-Živković Biljana; Mihić Vladimir (Temida, 2014)
In this paper, we explored the in-group and outer-group social distance towards sex workers and its relations to authoritarianism, social dominance orientation and self-respect. The sample consisted of 92 participants from the general population and 45 female sex workers (age 18-50). The instruments used were the Bogardus social distance scale, the Authoritarianism scale UPA-S, the Social dominance orientation scale and the Rosenberg self-respect scale. The results indicate a rather high social distance towards sex workers, including the distance by the general population being higher than the distance of the sex workers towards their own group. The correlation of authoritarianism and social distance was significant, as was the correlation between authoritarian aggressiveness and stoicism and social distance. The relationship between social dominance orientation and self-respect and social distance in our research has been statistically insignificant, however it demonstrates the expected trends. [Projekat Ministarstva nauke Republike Srbije, br. ON179002: Efekti egzistencijalne nesigurnosti na pojedinca i porodicu u Srbiji]